2020
DOI: 10.3390/md18030131
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence of Dermacoccus abyssi MT1.1 Isolated from the Challenger Deep of the Mariana Trench Reveals Phenazine Biosynthesis Locus and Environmental Adaptation Factors

Abstract: Dermacoccus abyssi strain MT1.1T is a piezotolerant actinobacterium that was isolated from Mariana Trench sediment collected at a depth of 10898 m. The organism was found to produce ten dermacozines (A‒J) that belonged to a new phenazine family and which displayed various biological activities such as radical scavenging and cytotoxicity. Here, we report on the isolation and identification of a new dermacozine compound, dermacozine M, the chemical structure of which was determined using 1D and 2D-NMR, and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Stress-related genes detected in the genome of Dermacoccus abyssi strain MT1.1 T , an isolate from the same sediment sample as the M. provocatoris strain, gave clues to how this piezotolerant strain became adapted to environmental conditions which prevail in sea-floor sediment of the Challenger Deep of the Mariana Trench [ 49 ]. In the present study, the genome of M. provocatoris strain MT25 T annotated using NCBI Genbank [ 24 , 25 , 26 ] pipeline was seen to harbor genes associated with a range of stress responses, notably ones linked with carbon starvation, cold shock response, high pressure, osmoregulation and oxidative stress ( Table S3 ), as was the case with the D. abyssi strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress-related genes detected in the genome of Dermacoccus abyssi strain MT1.1 T , an isolate from the same sediment sample as the M. provocatoris strain, gave clues to how this piezotolerant strain became adapted to environmental conditions which prevail in sea-floor sediment of the Challenger Deep of the Mariana Trench [ 49 ]. In the present study, the genome of M. provocatoris strain MT25 T annotated using NCBI Genbank [ 24 , 25 , 26 ] pipeline was seen to harbor genes associated with a range of stress responses, notably ones linked with carbon starvation, cold shock response, high pressure, osmoregulation and oxidative stress ( Table S3 ), as was the case with the D. abyssi strain.…”
Section: Resultsmentioning
confidence: 99%
“…The genome also contains gene deaD encoding an RNA helicase involved in cold shock response and adaptation [ 55 ]. The strain has genes associated with the synthesis of branch-chain and long chain polysaturated fatty acids that are linked to membrane fluidity and functionality at low temperatures [ 49 , 52 ], including fabF , fabG , fabH and fabI genes which are responsible for the biosynthesis of β -ketoacyl-ACP synthase II, 3-oxoacyl-ACP reductase, ketoacyl-ACP synthase III, enoyl-ACP reductase and enoyl-ACP reductase, respectively ( Table S3 ). The synthesis of low-melting point branched-chain and/or polyunsaturated fatty acids (PUFAs) is crucial as it allows organisms in cold environments to maintain membrane fluidity in a liquid crystalline state thereby allowing organisms to resist freeze-thaw cycles at low temperatures [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other notable genes mined from our metadata include drrABC, daunorubicin resistance genes 37 ; phzEFH, phenazine biosynthesis protein (biocontrol); 38 fepBCDEG, siderophore enterobactin or ferric enterobactin transport ATP-binding protein; 39 czcC, heavy metal efflux protein to resist the effect of cobalt, zinc and cadmium 40 ; soxBXYZ, sulfur oxidizing multi-enzyme genes 41 ; trehalose synthase, uptake of exogenous trehalose 42 and cysteine desulfurase family (sufs, iscs and csdA). 43…”
Section: Discussionmentioning
confidence: 99%
“…Seven novel phenazines, dermacozines A-G (4-10), as novel phenazines originating from Dermacoccus abyssi strains MT 1.1 T and MT 1.2 were reported by our group in 2010. Subsequently, another four new derivatives: dermacozines H-J (11)(12)(13) and dermacozine M (14) were isolated and reported with the contribution of our group in 2014 and 2020, respectively (Figure 2) [6][7][8]. These highly pigmented dibenzo annulated pyrazines has kept our interest piqued toward finding further unknown derivatives.…”
Section: Introductionmentioning
confidence: 95%
“…These highly pigmented dibenzo annulated pyrazines has kept our interest piqued toward finding further unknown derivatives. Properties of the previously discovered dermacozines include their radical scavenging ability, cytostatic activity against the K562 leukemia cell line, and theoretically calculated non-linear optical behavior [6][7][8][9]. Their IC 50 cytotoxic activities were reported to be in the range from 7 to 220 µM against the K562 chronic myelogenous leukemia cell line; structure-activity relationship studies revealed a strong connection between the phenazine core linked to a cyclic carboxylic anhydride with their increased activity, but no positive correlation was found in relation to the carboxamide, lactone, or benzoyl moieties [10].…”
Section: Introductionmentioning
confidence: 99%